[Ingham, Queensland : geographic ephemera collected by the National Library of Australia] - National Library of Australia
Material in the Geography and Travel ephemera collection covers significant information about the geography, history, and tourist activities of places in Australia, its Antarctic and island territories. This includes geographical features, national parks and reserves, regions, cities, towns, buildings and other man-made structures. The collection includes advertising material, pamphlets, price lists, tokens, area and accommodation guides, brochures, postcards, stickers, labels and tickets.
Related ephemera may also be held in the Trade catalogues and General ephemera sequences.
Keywords: Physical geography -- Queensland -- Ingham; Printed ephemera -- Australia; Tourism -- Queensland -- Ingham; Ingham (Qld.) -- Description and travel -- Miscellanea; Ingham (Qld.) -- History -- Miscellanea